2012
DOI: 10.1158/0008-5472.can-11-4090
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of IL-13 Receptor α2 in Colorectal Cancer Is Associated with Invasion, Liver Metastasis, and Poor Prognosis

Abstract: Autocrine secretion of cytokines by metastatic colorectal cancer cells and their role during invasion and liver homing has been poorly characterized. In this study, we used cytokine arrays to analyze the secretomes of poorly and highly metastatic colorectal cancer cells. Compared with poorly metastatic cancer cells, highly metastatic cells expressed increased levels of the immunosuppressive cytokines interleukin (IL)-4 and IL-13 in addition to increased surface expression of the high affinity IL-13 receptor IL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 37 publications
6
142
0
Order By: Relevance
“…Then, membranes were scanned and analyzed using Redfin, a 2D-gel image analysis software (Ludesi, Malmoe, Sweden) as described (23). Relative cytokine intensities were normalized in comparison to control spots on the same membrane and represented in arbitrary units.…”
Section: Methodsmentioning
confidence: 99%
“…Then, membranes were scanned and analyzed using Redfin, a 2D-gel image analysis software (Ludesi, Malmoe, Sweden) as described (23). Relative cytokine intensities were normalized in comparison to control spots on the same membrane and represented in arbitrary units.…”
Section: Methodsmentioning
confidence: 99%
“…The Ethical Committee of the Consejo Superior de Investigaciones Científicas (Madrid, Spain) approved the protocols used for experimental work with mice. Liver homing assays were performed as described previously (17). Briefly, 10 6 cells, KM12SM or RKO, transfected with vectors encoding for CDH17 WT, RAD, or empty vectors (mock) were inoculated intrasplenically into mice (n ϭ 3), which were euthanized after 24 h. RNA was isolated from mouse livers using TRIzol and retrotranscribed.…”
Section: Methodsmentioning
confidence: 99%
“…There is data that organic extraction from drinking water impairs liver function with the involvement of death receptor FAS and mitochondria-mediated apoptosis in rats [14]. Interleukin 13 receptor, α2 (IL13RA2) has high affinity to interleukin-13 and highly expressed in colorectal cancer, glioblastoma and other malignant tumors, is associated with invasion and liver metastasis [15,16]. Moreover, low-dose cadmium has growth-promoting effects on NPrEC cells and induces transient overexpression of genes with oncogenic and immunomodulation functions, including TNF and Il13ra2 [17].…”
Section: We Have Studied the Effect Of Chromium Disilicide And Titanimentioning
confidence: 99%
“…In this work, we studied the effect of titanium nitride and chromium disilicide nanoparticles on the expression of a subset of genes encoding different regulatory enzymes, receptors and transcription factors, which play an important role in various metabolic pathways and thus control proliferation and apoptosis [9,12,14,15,18,22,25]. For titanium dioxide nanoparticles, which are widely used in the number of applications, including cosmetic creams, toothpastes, and component of surgical implants, it was shown that long-term exposure to these nanoparticles led to accumulation of these nanoparticles in brain, over-proliferation of glial cells and significant changes in brain gene expressions as well as to neurogenic disease states in mice [1,2].…”
Section: Fig 3 Effect Of Prolonged Treatment Of Mice (2 Months) By mentioning
confidence: 99%
See 1 more Smart Citation